2016
DOI: 10.1080/01902148.2016.1190424
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin may attenuate lung inflammation in a rat model of meconium aspiration syndrome

Abstract: rhEPO pretreatment is associated with improved BAL fluid and serum cytokine levels. Pretreatment with rhEPO might reduce the risk of developing of meconium-induced derangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Downstream inflammatory mediators of the TLR4 signaling pathway, including TGF-β1 ( 30 ), TNF-α, IL-6 ( 31 ), IL-1β, IL-17A ( 32 ), MMP-9 and MMP-2 ( 33 ), promote the occurrence and development of MF ( 22 ). In the present study, it was demonstrated that EPO significantly decreased the release of TGF-β1, TNF-α, IL-6, IL-1β and IL-17A in serum and inhibited the expression of MMP-9 and MMP-2 in myocardial tissue of MF in rats subjected to AAC, which was consistent with the findings presented in other reports ( 11 , 34 , 35 ). The effects of EPO on inflammatory mediators may be key in attenuating MF.…”
Section: Discussionsupporting
confidence: 93%
“…Downstream inflammatory mediators of the TLR4 signaling pathway, including TGF-β1 ( 30 ), TNF-α, IL-6 ( 31 ), IL-1β, IL-17A ( 32 ), MMP-9 and MMP-2 ( 33 ), promote the occurrence and development of MF ( 22 ). In the present study, it was demonstrated that EPO significantly decreased the release of TGF-β1, TNF-α, IL-6, IL-1β and IL-17A in serum and inhibited the expression of MMP-9 and MMP-2 in myocardial tissue of MF in rats subjected to AAC, which was consistent with the findings presented in other reports ( 11 , 34 , 35 ). The effects of EPO on inflammatory mediators may be key in attenuating MF.…”
Section: Discussionsupporting
confidence: 93%
“…It is reported that 8 hours post the treatment of meconium, approximately 70% apoptotic bodies are found in the airway epithelial cells and the apoptosis is also found in the alveolar epithelial cells [24,25]. In the present study, a MAS model was successfully established on rats, which was verified by the symptoms, such as increased W/D ratio, elevated production of inflammatory factors, and aggravated apoptotic state in the lung tissues, which was consistent with the pathological changes described previously [26,27]. In addition, according to the results of HE staining, significant infiltration of leukocytes and large amounts of alveolar exudates were observed in the lung tissues from MAS rats, which corresponded to the description by Turhan [7].…”
Section: Discussionsupporting
confidence: 91%
“…The aim of MAS treatment focuses on minimizing ongoing injury, maintaining oxygenation, and reducing inflammation. Various anti-inflammatory drugs (such as glucocorticoids, phosphodiesterase inhibitors, angiotensin-converting enzyme inhibitors, erythropoietin) have been tested as possible MAS therapies [6][7][8][9] . However, therapy of MAS has controversies to show beneficial effects.…”
Section: ■ Introductionmentioning
confidence: 99%